Analysis of cold atmospheric-pressure bio-medicine plasmas by using UV absorption spectroscopy - Thana Y. (2017)
© 2016 Elsevier B.V. Cold atmospheric pressure plasma consists of OH, O, O 3 , NO, and NO 2 radicals is currently well known in biomedical applications. This is due to its ability to kill microbes and stimulating productions of new cells. For such applications, the density measurement of any radical in the plasma is needed. In this work, we have applied ultraviolet (UV) absorption spectroscopy with micro stage XY table add-on to investigate and measure of the density of hydroxyl (OH) radicals from an in-house Hybrid Jet-Floating electrode plasma head as well as the radial distribution on the surface. Furthermore, the OH concentration of a needle-typed atmospheric-pressure plasma jet was carried out to perform a comparison. The hydroxyl radical density and its distribution have been investigated and measured to be the maximum value of 1.68 × 10 15  cm − 3 with Ar flow rate 8 l/min and 2.17 × 10 15  cm − 3 with Ar flow rate 3.5 l/min for the Medi-Plasma head and the needle-typed cold atmospheric-pressure plasma jet, respectively. The maximum OH concentration of Medi-Plasma head occurs at the origin and decrease as radial distance increases while the farthest density for plasma jet is obtained at 0.5 mm of the radial distance.